Who Cares? How Students View Faculty and Other Adults in US Higher Education - George R. Goethals; Laurie C. Hurshman; Adam C. Sischy; Gordon C. Winston; Georgi Zhelev; David J. Zimmerman (Williams College, Williams Project on the Economics of Higher Education (WPEHE), 2003)
Using Mellon Foundation's College and Beyond survey of alumni from 34 colleges and universities spanning 40 years, Clotfelter found that those who reported that someone "... besides students [took] a special interest in you or your work" also reported greater general satisfaction with their college and, concretely, made larger alumni gifts. This paper uses those same data to see who it was who is reported to have cared - faculty, coaches, deans, ... - how that differed by institutional type - public research universities, coed or women's liberal arts colleges, Ivy universities … - and how it changed over time - for entering cohorts of 1951, 1976, and 1989. Some of the results may be predictable - for instance, that faculty are the main 'care givers' in all times and places - while others are unexpected - that there's no indication of a decline in the faculty role over time, for instance, or that athletes, while they find coaches more caring than do non-athletes, still report that faculty are more caring than coaches.
Keywords: 330; Hochschule; Meinung; USA